Normal-state negative longitudinal magnetoresistance and Dirac-cone-like dispersion in PtPb4 single crystals: a potential Weyl-semimetal superconductor candidate. (20th September 2021) - Wang, Li-Min; Lin, Sheng-En; Shen, Dong; Chen, I-Nan
Abstract: Magnetotransport measurements of PtPb4 single crystals with the T c of ∼2.80 K reveal pronounced exotic topological nature. An anomalous negative longitudinal magnetoresistance (MR) related to the chiral anomaly and a linear-like transverse MR examined within the framework of quantum MR theory were studied. Results indicate the presence of chiral-anomaly-induced quantum transport associated with the Weyl states and show a Dirac-cone-like band dispersion in PtPb4 . This work reveals the drastic impact of the concept that the surface electrons in a Weyl fermion state may dominate the normal-state magnetotransport in PtPb4, leading to the conclusion that PtPb4 can be a Weyl-semimetal superconductor candidate.